Pengukuran Suhu Permukaan Menggunakan Pancaran Spektral dari Citra Satelit: Studi Kasus di Banda Aceh - Putra Arafat Taqwallah; Ichwana Ramli; Alia Rizkia (Department of Agricultural Engineering, Syiah Kuala University, 2021)
Abstrak. Tingginya tingkat urbanisasi menyebabkan meluasnya wilayah perkotaan dan menciptakan daerah keras yang mengakibatkan suhu tinggi di wilayah perkotaan, termasuk Banda Aceh. Permasalahan ini tentu menimbulkan ketidaknyamanan bagi masyarakat Banda Aceh. Beberapa penelitian melaporkan bahwa suhu udara yang terlalu tinggi dapat menyebabkan masalah kesehatan yang serius di masyarakat. Suhu permukaan Banda Aceh diukur menggunakan Spectral Radiance dari Satellite Imager, kemudian dibandingkan dengan data yang diukur langsung di lokasi penelitian. Hasil menunjukkan suhu udara di Banda Aceh berkisar antara 22,32°C hingga 34,86°C. Selain itu, terjadi korelasi antara penggunaan ruang dengan tingkat suhu udara Banda Aceh berdasarkan parameter hard area dan vegetasi. Namun, hanya variabel jarak dengan badan air yang memiliki korelasi signifikan terhadap perubahan tingkat suhu.Surface Temperature Distribution Using Spectral Radiance from Satellite Imagery: A Case Study in Banda AcehAbstract. The high rate of urbanization will have an effect on land change. The increasing number of buildings and lack of green open space will hinder the direction of wind speed, cause inconvenience to the public. The purpose of this study was to determine the distribution of surface temperature in the city of Banda Aceh based on the spectral emission of Landsat images from vegetation density, distance from the river, and built-up area. The air temperature data were obtained using the classification method from the digital number value of the Landsat image to the spectral radiance and then converted into air temperature. The density of the built-up area was analyzed from the Normalized Difference Vegetation Index (NDBI) and the density of the vegetation was analyzed from the Normalized Difference Vegetation Index (NDVI). The air temperature distribution map from the image is divided into 3 zones that are densely populated (built-up area), vegetation and distance to water bodies to be measured directly in the field. The air temperature from the lansat 8 images ranged from 22.32°C to 34.86°C. The zone with a distance of 3,457 km from a water body, with less vegetation density (0) and a built-up area of 0.16-0.23 has a temperature of 31.96oC -32.45oC, while the zone with a water body distance of 1,255 km with a built-up area below zero and vegetation has a temperature of 25.82oC-27.09oC. Based on the parameters of space use (vegetation and built-up area) and the distance between the zone and the water body, it has an influence on the distribution of air temperature in the city of Banda Aceh.